PENGGUNAAN STRATEGI QUESTION STUDENT HAVE DALAM MENINGKATKAN MOTIVASI BELAJAR MATA PELAJARAN IPS MATERI PENINGGALAN SEJARAH HINDU-BUDHA KELAS V SDN II BUBULAN BOJONEGORO - Purnamasari, Lina (Journal Of Islamic Elementary School (JIES), 2017)
In this study, several problem formulations were formulated, among others: How to use the Question Student Have strategy in social studies subject matter from class V Hindu-Buddhist heritage in SD Negeri II Bubulan Bojonegoro? As well as how to increase learning motivation with the Question Student Have strategy in social studies, the material of Hindu-Buddhist heritage in grade V SD Negeri II Bubulan Bojonegoro? Starting from this problem, this study aims to: To determine the use of the Question Student Have strategy in social studies subjects, material of Hindu-Buddhist history in class V SD Negeri II Bubulan Bojonegoro and to determine the increase in learning motivation with the Question Student Have strategy in social studies subjects, historical heritage material Hindu-Buddhist class V SD Negeri II Bubulan Bojonegoro. This researcher is a classroom action research with Kurt Lewin’s model which states that in one cycle there are four main steps, namely: planning, acting, observing and reflecting. Researchers used data inference techniques, namely questionnaires, interviews, observation of teacher and student activities. The data analyzed were data related to student learning motivation. The application of the Question Student Haveprategy in cycle I in the social studies subject matter of Hindu-Buddhist heritage in the fifth grade students of SDN II Bubulan Bojonegoro was carried out well, it’s just that some students are still less active in learning. In the second cycle there was an increase because learning was carried out by giving ice breaking, giving question cards and flash cards to the Question Student Have strategy. From the calculation using this technique, the result is the use of the Question Student Have strategy to increase learning motivation to run well. It can be seen in the increase in teacher activity in cycle I from 75 to 90 in cycle II and student activity in cycle I of 67 up to 88.33. There was an increase in learning motivation from pre-cycle to cycle I and cycle II. as for the pre-cycle students’ learning motivation was 17.64%. Then in the first cycle it increased to 70.6% and in the second cycle it increased to 88.23%.